An exploratory study of diet in childhood and young adulthood and adult-onset multiple sclerosis. (September 2021) - Black, Lucinda J; Hetherton, Sarah; Forkan, Michaela; Gonzales, Edlin G; Smith, Jessica B; Daly, Alison; Lucas, Robyn M; Langer-Gould, Annette
There is little evidence on the role of diet in childhood/adolescence and multiple sclerosis (MS) in adulthood. The MS Sunshine Study recruited adults with recent-onset MS ( n  = 602) and matched controls ( n  = 653). Of these, 84% provided dietary recall for specific ages between childhood and young adulthood (6–10, 11–15 and 16–20 years). We used logistic regression to test associations between age-specific diet and case-control status. Consumption of fruit (all ages), yoghurt (all ages) and legumes (11–15 years) was associated with lower probability of adult-onset MS (all p  < 0.05). These results suggest that healthy dietary habits between childhood and young adulthood may reduce MS risk.